TITER EKDISON LOBSTER HIJAU PASIR (Panulirus homarus L.) PADA FASE PREMOLTING AKHIR - Muhsinul Ihsan; Trijoko Trijoko; Nastiti Widjayanti (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
Spiny Lobster, Panulirus homarus, farming is very potential to be developed in Lombok Island, but physiological aspects such as nutrient needs and growth hormone, especially ecdysone titer, were little known. This research aimed to determine the ecdysone titer of Panulirus homarus during the last pre-molting phase. This study was conducted as a quasi-experiment with one group post-test design. The lobsters used in this experiment have the length of carapacs and the body weight of 1.5–2.0 cm and 4.33–5.77 g respectively. The lobster fed for 42 days with gel pellets three times a day before ecdysone titer measurement. The ecdysone hormone was then isolated from the second segment of the abdomen on the basal of the fifth pereiopod. Ecdyson titer was measured by using High-Performance Liquid Chromatography (HPLC). The result showed that the titer of ecdysone was 5.27 µg/ml hemolymph. The titer of ecdysone was found higher compared to previous research on Homarus americanus; this result suggested that the spiny lobster Panulirus homarus needs a higher amount of ecdysone hormone to initiate the molting process.